Conservation of rangelands in mountainous regions of Kyrgyzstan - Kenzhaev I. G.; Matisakov T. K.; Rasakhodzhaev B. S.; Erkebaev T. K.; Kubatov N. K. (E3S Web of Conferences)
At present, there is an intensive deterioration of pastures located in mountainous and foothill regions of the Kyrgyz Republic. Therefore, preservation of pastures from degradation through the use of irrigation systems is an urgent task. The object of the conducted research is an autonomous water lifting plant, operating on the water head of mountain rivers and designed for irrigation of pastures and rainfed lands. The purpose of the conducted research is to determine the performance of the water lifting unit in real mountain conditions. The conducted research has established that pasture preservation and improvement can be achieved through irrigation measures using water-lifting installations. The article describes the design and principle of operation of the developed autonomous water lifting plant, working on the water head of mountain rivers. According to the results of the conducted research rational values of pressure of injection, height of water lifting and productivity of the installation are established.